STUDIES OF ASTHMA CONTROL IN PATIENTS WITH METABOLIC SYNDROME (World Science, 2024)
Every day, a practitioner is faced with the problem of patient comorbidity. Bronchial asthma is a common problem, as is metabolic syndrome. Due to the increase in allergic diseases and lifestyle changes, patients may have a combination of metabolic syndrome and bronchial asthma. This combination has been shown to aggravate the course of asthma. Therefore, we wanted to confirm or refute this with our study. The study design included 94 patients with a diagnosis of asthma. A comparative analysis of the spirographic study data revealed that patients with asthma + MetS had statistically significant differences (p